Update on the treatment navigation for functional cure of chronic hepatitis B: Expert consensus 2.0 - Di Wu; Jia-Horng Kao; Teerha Piratvisuth; Xiaojing Wang; Patrick T.F. Kennedy; Motoyuki Otsuka; Sang Hoon Ahn; Yasuhito Tanaka; Guiqiang Wang; Zhenghong Yuan; Wenhui Li; Young-Suk Lim; et al. (Clinical and Molecular Hepatology)
As new evidence emerges, treatment strategies toward the functional cure of chronic hepatitis B are evolving. In 2019, a panel of national hepatologists published a Consensus Statement on the functional cure of chronic hepatitis B. Currently, an international group of hepatologists has been assembled to evaluate research since the publication of the original consensus, and to collaboratively develop the updated statements. The 2.0 Consensus was aimed to update the original consensus with the latest available studies, and provide a comprehensive overview of the current relevant scientific literatures regarding functional cure of hepatitis B, with a particular focus on issues that are not yet fully clarified. These cover the definition of functional cure of hepatitis B, its mechanisms and barriers, the effective strategies and treatment roadmap to achieve this endpoint, in particular new surrogate biomarkers used to measure efficacy or to predict response, and the appropriate approach to pursuing a functional cure in special populations, the development of emerging antivirals and immunomodulators with potential for curing hepatitis B. The statements are primarily intended to offer international guidance for clinicians in their practice to enhance the functional cure rate of chronic hepatitis B.